PENGARUH MOTIVASI KERJA DAN LOYALITAS KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. CISARUA MOUNTAIN DAIRY - ADE CHAIRUNNISA; JAENUDIN JAENUDIN (Institut Bisnis Muhammadiyah Bekasi, 2020)
This study aims to determine the effect of work motivation and loyalty on the work productivity of PT. Cimory employees, and the research was conducted directly at the PT. Cimory factory in the Sentul industrial area. This research is a descriPT.ive study with a quantitative approach, the data collection techniques used in this study are questionnaires and direct interviews with related parties according to the research objectives. The research subjects used were employees of PT. Cimory as many as 100 respondents. The analysis technique uses the classical assum PT.ion test, multiple regression with the model feasibility test, namely the t test and f test. The results showed that from 100 respondents it was known that by means of the t test (partial), the variable of work motivation on the work productivity of PT. Cimory employees obtained a significant influence, with a value of t count 4.021 1.660 t table. As for the job loyalty variable partially there is no significant effect on the work productivity of PT. Cimory employees, with a value of t count 0.462 1.660 t table. While the f test (simultaneous) work motivation and job loyalty have a significant effect on the work productivity of PT. Cimory employees, with a calculated f value of 8.108 3.09.